Preschoolers Understand the Moral Dimension of Factual Claims - Fedra, Emmily; Schmidt, Marco F. H. (Frontiers in Psychology, 2018)
Research on children's developing moral cognition has mostly focused on their evaluation of, and reasoning about, others' intrinsically harmful (non-)verbal actions (e.g., hitting, lying). But assertions may have morally relevant (intended or unintended) consequences, too. For instance, if someone wrongly claims that “This water is clean!”, such an incorrect representation of reality may have harmful consequences to others. In two experiments, we investigated preschoolers' evaluation of others' morally relevant factual claims. In Experiment 1, children witnessed a puppet making incorrect assertions that would lead to harm or to no harm. In Experiment 2, incorrect assertions would always lead to harm, but the puppet either intended the harm to occur or not. Children evaluated the puppet’s factual claim more negatively when they anticipated harmful versus harmless consequences (Experiment 1) and when the puppet’s intention was bad versus good over and above harmful consequences (Experiment 2). These findings suggest that preschoolers’ normative understanding is not limited to evaluating others’ intrinsically harmful transgressions, but also entails an appreciation of the morally relevant consequences of, and intentions underlying, others’ factual claims.